O2/HMDSO‐Plasma‐Deposited Organic–Inorganic Hybrid Film for Gate Dielectric of MgZnO Thin‐Film Transistor. Issue 1 (5th December 2013) - Tsai, Chih‐Hung; Li, Yun‐Shiuan; Cheng, I‐Chun; Chen, Jian‐Zhang
<x xml:space="preserve">Abstract</x> An organic–inorganic hybrid film is deposited from O2/HMDSO plasma. The SiOSi/SiCH3 FTIR absorption ratio of this film increases with the process power and O2/HMDSO precursor flow ratio, resulting in a more inorganic‐like film. This hybrid film is used as the gate dielectric of MgZnO TFTs. As the SiOSi/SiCH3 FTIR absorption ratio of the gate dielectric increases, the gate leakage current decreases, on/off current ratio increases, threshold voltage increases, and subthreshold swing increases. High SiCH3 bonding content in the gate dielectric improves TFT switching but deteriorates gate insulation, resulting in increased gate leakage current and decreased on/off current ratio.<inline-graphic xlink:href="ark:/27927/pgg3zvzmt7h" content-type="ppap201300107-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />